Competing aggregation pathways for monoclonal antibodies. Issue 6 (12th February 2014) - Wu, Haixia; Kroe-Barrett, Rachel; Singh, Sanjaya; Robinson, Anne S.; Roberts, Christopher J.
Abstract : Aggregation is mediated by local unfolding to allow aggregation "hot spot(s)" to become solvent exposed and available to associate with a hot spot on another partially unfolded protein. Historically, the unfolding of either the crystallizable fragment (Fc) or the antigen binding fragment (Fab) regions of a given monoclonal antibody (MAb) has been implicated in aggregation, with differing results across different proteins. The present work focuses on separately quantifying the aggregation kinetics of isolated Fc, isolated Fab, and intact MAb as a function of pH under accelerated (high temperature) conditions. The results show that both Fab and Fc are aggregation prone and compete within the same MAb. Abstract : Experimental intrinsic aggregation rates of partially unfolded Fc and Fab. Competition between Fab‐ and Fc‐mediated aggregation is pH‐dependent. Hot spots within conserved regions of MAbs may also need to be improved.